Pyrolusite-rich tailings from Nikopol against anoxia? - Schuiling, R.D. (Мінералогічний журнал, 2011)
Anoxia in marine basins is a problem, or is feared to become a problem in several locations. A straightforward remediation would be to blow large volumes of oxygen (or air) into those sub-oxic waters, but that is a tiresome and costly affair. By introducing a solid oxygen donor, it should be possible to attack the anoxia problem for a reasonable period of time in a single and simple operation. An obvious and cost-effective choice would be the use of the mineral pyrolusite (MnO₂). This is one of the commonest manganese ore minerals, and hundreds of millions of tons of manganese tailings containing this mineral are stored in tailings near manganese mines all over the world. A well-known example of such tailings can be found in the manganese mining district near Nikopol/Ukraine. Its use has no harmful effect, as the mineral contains no heavy metals, and even its pore waters are of drinking water quality. The major problem is probably that the reaction of MnO₂ is rather sluggish.